BIM aplicado a obras de infraestrutura (BiiM) : mini e pequenas centrais hidrelétricas - Radüns, Caroline Daiane (2013)
Infrastructure is a set of essential systems to support the company as it promotes quality of life, work and leisure, resulting in economic and social development. At present, there is a deficit in infrastructure, which should be supplied with larger investments in the sector, and also the application of new techniques for controlling the interaction between the stages of the life cycle of this type of unit construction. The infrastructure is ranked systems, one of which is energy system. This is divided into sectors: generation, transmission, distribution and final consumption of energy. In Brazil most of the energy generated comes from hydroelectric plants, so it is important to give attention to projects in energy infrastructure system in this area, here called horizontal constructions. It is also one of the areas with higher investment forecast. Current techniques for development of these projects offer limitations, as lack of standardization systems in the building, and no interaction between designers information becomes fragmented, and generates projects and documentation leading to errors and rework, and open doors for embezzlement because much of the funding comes from government investments. Projects in this sector require specialized companies and using processes that ensure quality and certainty of the project and the demand to be supplied with agility, cost reduction, ease of maintenance and also the transparency of the actions of the public sector. To meet this demand, one of the processes that can be applied is the BIM (Building Information Modeling). BIM is an integrated process that facilitates the exchange of information among those involved in a project throughout its lifecycle. The objective of this research is to propose the application of BIM in infrastructure projects, focusing on the energy system - sector power generation. For this, a study of BIM and the characteristics of the life cycle of hydropower plants was performed, and formulated a model of implementation of BIM on infrastructure systems, forming Infrastructure Building Information Modeling (Biim). We applied the Biim the energy system - sector power generation in mini and small hydropower, thus showing the steps of modeling and resulting from that application